Social network analysis in football: a systematic review of performance and tactical applications - Alves, R.; Dias, G.; Nunes, N. A.; Querido, S. M.; Vaz, V. (Frontiers in Psychology, 2025)
Introduction: This systematic review aims to critically examine the application of social network analysis (SNA) in football, with a focus on its contribution to evaluating team performance, tactical behavior, and player interactions.